Prevalence and molecular epidemiology of mcr-mediated colistin-resistance Escherichia coli from healthy poultry in France after national plan to reduce exposure to colistin in farm - Perrin-Guyomard, Agnès; Houée, Paméla; Lucas, Pierrick; Felten, Arnaud; Le Devendec, Laetitia; Chauvin, Claire; Kempf, Isabelle (Frontiers in Microbiology, 2023)
Within the 2007-2014 programme for the surveillance of antimicrobial resistance (AMR) in livestock in France, mcr-1 prevalence average in commensal Escherichia coli was found to be 5.9% in turkeys and 1.8% in broilers, indicating that mobile colistin resistance had spread in farm animals. In 2017, the French national Ecoantibio2 plan was established to tackle AMR in veterinary medicine, with the objective of a 50% reduction in exposure to colistin in farm animals within 5 years (from 2014-2015 to 2020). Our objective was to update data concerning the prevalence and molecular epidemiology of colistin resistance, in consideration of colistin sales in poultry production in France. Antimicrobial susceptibility of commensal E. coli isolated from broilers and turkeys at slaughterhouse was determined by broth micro-dilution. The mcr genes were screened by polymerase chain reaction (PCR). Whole genome sequencing (WGS) was used to investigate the genetic diversity of colistinresistant isolates. Transformation experiments enabled identification of the mcr-bearing plasmid replicon types. The correlation between prevalence of colistin resistance and colistin usage data was explored statistically. In 2020, in France, the resistance prevalence to colistin in poultry production was 3% in turkeys and 1% in broilers, showing a significant highly positive correlation with a -68% decrease of poultry exposure to colistin since 2014. Only the mcr-1 gene was detected among the colistin-resistant E. coli. More than 80% of isolates are multi-drug resistant with 40% of isolates originating from turkeys and 44% originating from broilers co-resistant to the critically important antimicrobial ciprofloxacin. Most of the strains had no clonal relationship. The mcr gene was located in different plasmid types, carrying various other AMR genes. The decrease in colistin resistance among poultry in France can be considered a positive outcome of the national action plans for reduced colistin usage.